Expert knowledge elicitation with SHELF: skills and resources - O'Hagan, Anthony (Henry Stewart Talks, 2023)
SHELF, Expert knowledge elicitation with SHELF, Skills and resources, The facilitator and recorder in the elicitation workshop, SHELF multivariate elicitation tools, Quantities of Interest (QoI) in elicitation, The extension, copula, and Dirichlet methods